Intraoperative lactate levels and postoperative complications of pediatric cardiac surgery - Alves, Rodrigo Leal; Aragao e Silva, Andre Luiz; de Castro Kraychete, Nadja Cecilia; Campos, Guilherme Oliveira; Martins, Marcelo de Jesus; Módolo, Norma Sueli Pinheiro [UNESP] (Wiley-Blackwell, 2012)
Objectives: Correlate arterial lactate levels during the intraoperative period of children undergoing cardiac surgery and the occurrence of complications in the postoperative period. Aim: Arterial lactate levels can indicate hypoperfusion states, serving as prognostic markers of morbidity and mortality in this population. Background: Anesthesia for cardiac pediatric surgery is frequently performed on patients with serious abnormal physiological conditions. During the intraoperative period, there are significant variations of blood volume, body temperature, plasma composition, and tissue blood flow, as well as the activation of inflammation, with important pathophysiological consequences. Methods/Materials: Chart data relating to the procedures and perioperative conditions of the patients were collected on a standardized form. Comparisons of arterial lactate values at the end of the intraoperative period of the patients that presented, or not, with postoperative complications and frequencies related to perioperative conditions were established by odds ratio and nonparametric univariate analysis. Results: After surgeries without cardiopulmonary bypass (CPB), higher levels of arterial lactate upon ICU admission were observed in patients who had renal complications (2.96 vs 1.31 mm) and those who died (2.93 vs 1.40 mm). For surgeries with CPB, the same association was observed for cardiovascular (2.90 mm x 2.06 mm), renal (3.34 vs 2.33 mm), respiratory (2.98 vs 2.12 mm) and hematological complications (2.99 vs 1.95 mm), and death (3.38 vs 2.40 mm). Conclusion: Elevated intraoperative arterial lactate levels are associated with a higher morbidity and mortality in low- and medium-risk procedures, with or without CPB, in pediatric cardiac surgery.
Keywords: pediatric cardiac surgery; extracorporeal circulation; lactate; morbidity; mortality